DETERMINAN AND SPEED OF ADJUSTMENT DEBT TO EQUITY RATIO PADA PERUSAHAAN MANUFAKTUR INDEKS LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2023 - M.Rizal; Adler Haymans Manurung; Edward Efendi; Muhammad Richo Rianto; Jhonni Sinaga (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the determinants of debt of manufacturing industrial companies in Indonesia listed on the Indonesia Stock Exchange for the 2017 - 2023 period. The data used in this research is secondary data. This data is quantitative data obtained from the Indonesia Stock Exchange (BEI) with shares included in the LQ45 Index in the form of annual financial reports for the period 2017 - 2023. The research sample was 36 companies obtained using the outlier test. The data analysis technique used is multiple linear regression analysis and hypothesis testing using a partial t test, simultaneous F test and coefficient of determination test. The data analysis technique was carried out using the Eviews10 for Windows program. The research results show that Speed of Adjustment, Growth, Size (Market Capitalization) and Net Profit Margin together (simultaneously) have a significant effect on the Debt to Equity Ratio.